ANALISIS PERSEPSI SISWA TERHADAP PENGGUNAAN MEDIA QUIZIZZ DALAM PEMBELAJARAN AQIDAH AKHLAK DI MI ISLAMIYAH GUNUNG GENI BANYUANYAR PROBOLINGGO - Fakhrul Hiday Rasyid; Nur Fatimah, Farich Purwanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ResultsThe development of information technology has brought significant changes in the world of education, including in learning methods and media. One of the popular interactive learning media is Quizizz. This article aims to analyze students' perceptions of the use of Quizizz media in the subject of Aqidah Akhlak. Using a descriptive qualitative approach, data were collected through observation, interviews, and distributing questionnaires to students. The results showed that most students had a positive perception of the use of Quizizz because this media was considered fun, interactive, and helped to understand the material of Aqidah Akhlak more effectively. Keywords: Students, quizz media, MI Islamiyahl The study showed that most students had a positive perception of the use of Quizizz because this media was considered fun, interactive, and helped to understand the material of Aqidah Akhlak more effectively.